Helping Minority Students From Rural and Disadvantaged Backgrounds Succeed in Nursing: A Nursing Workforce Diversity Project - Marian Tabi (Rural Nurse Organization; Binghamton University, 2016)
Introduction: Retention and graduation rates among minority nursing students continue to be a challenge in nursing education.  While multiple strategies have been implemented to increase diversity in the nursing workforce, disadvantaged minorities from rural backgrounds often face challenges that create barriers to their academic success. The RUN 2 Nursing program, a nursing workforce diversity program funded by the U.S Department of Health and Human Services, recognized the need to use faculty mentoring and peer tutoring to make a difference in the academic success of minority nursing students from rural and disadvantaged backgrounds. Methods: Data were collected from a convenience sample of 62 minority students and 22 faculty mentors. Descriptive statistics including mean and standard deviation were used to report the aggregate data from the mentoring survey. Findings: Retention rate of 93% and NCLEX-RN pass rate of 93% were achieved for the minority students enrolled in the nursing workforce diversity project. These findings suggest the peer and faculty mentoring were effective support strategies. Conclusions: Preparing a well-skilled, competent and diverse workforce of health professionals is a priority in eliminating health disparities, particularly in rural and medically underserved communities. NWD programs, such as the RUN 2 Nursing program, with well-structured mentoring and peer tutoring services can make a difference in nursing workforce diversity.  Keywords:  Faculty mentoring, minorities, nursing workforce diversity, peer tutoring, rural, disadvantaged  DOI:  http://dx.doi.org/10.14574/ojrnhc.v16i1.362